2002
DOI: 10.1007/s10350-004-7254-1
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Colon Surveillance in the Transplant Population

Abstract: Because of an equivalent incidence of adenomatous polyps compared with the general population, current screening criteria should be used in patients posttransplant. Transplant patients are not more likely to develop metachronous polyps than the general population. Therefore, posttransplant polyp surveillance should not be more frequent than currently recommended for nontransplant patients with adenomatous polyps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 18 publications
(21 reference statements)
1
24
0
Order By: Relevance
“…These guidelines recommend annual fecal occult Review Kan, Gill & Wiseman blood testing and sigmoidoscopy every 5 years or total colon examination either by colonoscopy or barium enema every 5-10 years. These guidelines are consistent with the observations of Parikshak et al, who reported that the incidence of adenomatous polyps (the precursor lesions for CRC) was not increased in PRTP compared with the general population [33]. For high-risk individuals, such as those with a family history of CRC, a previous CRC diagnosis, or history of inflammatory bowel disease, the guidelines suggested that more intensive screening could be carried out at the discretion of the treating physician [33].…”
Section: Crc Screeningsupporting
confidence: 75%
See 1 more Smart Citation
“…These guidelines recommend annual fecal occult Review Kan, Gill & Wiseman blood testing and sigmoidoscopy every 5 years or total colon examination either by colonoscopy or barium enema every 5-10 years. These guidelines are consistent with the observations of Parikshak et al, who reported that the incidence of adenomatous polyps (the precursor lesions for CRC) was not increased in PRTP compared with the general population [33]. For high-risk individuals, such as those with a family history of CRC, a previous CRC diagnosis, or history of inflammatory bowel disease, the guidelines suggested that more intensive screening could be carried out at the discretion of the treating physician [33].…”
Section: Crc Screeningsupporting
confidence: 75%
“…Radiotherapy is commonly used as adjuvant therapy for rectal cancer [33]. In PRTPs the location of the renal transplant often places it within the field of pelvic irradiation and options for reducing the chance of graft injury include modification of the radiation dose/field or surgically repositioning the graft away from the radiation field [33].…”
Section: Treatment Of Crc In Prtpsmentioning
confidence: 99%
“…19 Studies examining the role of colonoscopic surveillance in the TXP population have reported mixed results, with some suggesting increased surveillance and others advocating standard guidelines followed for non-TXP patients. [20][21][22] However, a large number of TXP patients are exposed to chronic immunosuppression well before their first colonoscopy. Previously, we have reported that aggressive upper-endoscopy in liver TXP patients resulted in diagnosis of gastric cancers at an earlier stage than the general population, and that early stage at diagnosis correlated with excellent survival rates despite immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 Better detection of gastroduodenal and colonic disease seems to be mandatory, by means of well defined preoperative screening protocols of all patients with end stage renal disease who may be candidates for transplantation, or for those who may have already been transplanted. 12 In general, these patients are more susceptible to perioperative complications. Immunosuppression can lead to a higher infection rate; moreover surgical stress can lead to more immunosuppression.…”
Section: Discussionmentioning
confidence: 99%